Toward Standardizing a Lexicon of Infectious Disease Modeling Terms - Milwid, Rachael; Steriu, Andreea; Arino, Julien; Heffernan, Jane; Hyder, Ayaz; Schanzer, Dena; Gardner, Emma; Haworth-Brockman, Margaret; Isfeld-Kiely, Harpa; Langley, Joanne M.; Moghadas, Seyed M. (Frontiers in Public Health, 2016)
Disease modelling is increasingly being used to evaluate the effect of health intervention strategies, particularly for infectious diseases. However, the utility and application of such models are hampered by the inconsistent use of infectious disease modelling terms between and within disciplines. We sought to standardize the lexicon of infectious disease modelling terms, and develop a glossary of terms commonly used in describing models’ assumptions, parameters, variables, and outcomes. We combined a comprehensive literature review of relevant terms with an online forum discussion in a virtual community of practice, mod4PH (Modelling for Public Health). Using a convergent discussion process and consensus amongst the members of mod4PH, a glossary of terms was developed as an online resource. We anticipate that the glossary will improve inter- and intra-disciplinary communication, and will result in a greater uptake and understanding of disease modelling outcomes in heath policy decision-making. We highlight the role of the mod4PH community of practice and the methodologies used in this endeavour to link theory, policy, and practice in the public health domain.